Mineralização do carbono e do nitrogênio no solo com o uso de lodo de esgoto e palha de aveia - Cas, Véra Lúcia Simon da (2009)
The use of sewage sludge in the agricultural is an organic recycle alternative material in the soil. The CONAMA resolution 375/2006 indicates that in certain relief condition the sewage sludge could be applied without soil incorporation, making it possible to use in areas with no-till. The present study was carried out with the aim to evaluate nitrogen and carbon mineralization dynamics during the sewage sludge and oat straw decomposition in the surface or in the soil incorporation. The treatments consisted of the sewage sludge application, in the presence and in the absence of oat straw, with and without soil incorporation. During 110 days of incubation, the CO2 emission and the mineral N dynamics was evaluated after the organic materials soil application. The sewage sludge soil incorporation not affected by the C and N mineralization. In the treatment with only sewage sludge 30% of C and 50% of N added with the sewage sludge were mineralized in 110 days. The application of sewage sludge with the straw of oats increased the C mineralization of oat straw only when those organic materials remained in the soil surface. The N immobilization is not affected by the sewage sludge incorporation and oat straw in the soil, however it is stimulated in the presence of the straw.